Rule of law and cause in the Italian system of administrative acts (Discourse of Law and Administration, 2023)
The work analyzes the problem of the cause of administrative acts in a general theory perspective. Regarding to the doctrine between the World Wars, it studies this category in the contemporary italian legal system, approaching some opinions particularly problematic.
Keywords: causa; public administration; administrative function; rule of law